Chronic active Epstein-Bar virus infection complicated by pulmonary artery hypertension. Issue 2 (February 2023) - Misaki, Yukiko; Minakata, Daisuke; Ibe, Tatsuro; Gomyo, Ayumi; Yoshimura, Kazuki; Kimura, Shun-ichi; Nakamura, Yuhei; Kawamura, Masakatsu; Kawamura, Shunto; Takeshita, Junko; Yoshino, Nozomu; Matsumi, Shimpei; et al.
Abstract: Chronic active Epstein-Bar virus infection (CAEBV) is known to cause various symptoms. Although pulmonary artery hypertension (PAH) has been reported as a cardiovascular complication of CAEBV, the mechanisms of PAH and the effects of treatment have not been fully elucidated. We experienced 4 adult patients with CAEBV complicated by PAH. All of them received treatment for PAH with a vasodilator followed by chemotherapy with or without allogeneic hematopoietic cell transplantation for CAEBV. In all of these patients, the transtricuspid pressure gradient improved under treatment with vasodilator, and further improvement was observed under treatment for CAEBV in 3 patients. Autopsy was performed in 2 patients, which revealed EBER-positive cells and a change in the pulmonary artery at each stage in the pathology. In conclusion, EBV-infected cells can cause vasculitis and finally PAH. However, PAH complicated with CAEBV can be improved by PAH medication and treatment of CAEBV.